Anti-tumor effects of Skp2 inhibitor AAA-237 on NSCLC by arresting cell cycle at G0/G1 phase and inducing senescence. (July 2022) - Liu, Jinyi; Zheng, Xiangjin; Li, Wan; Ren, Liwen; Li, Sha; Yang, Yihui; Yang, Hong; Ge, Binbin; Du, Guanhua; Shi, Jianyou; Wang, Jinhua
Abstract: Lung cancer is by far the leading cause of cancer death worldwide, and 85% of patients are diagnosed with non-small cell lung cancer (NSCLC), which is still very difficult to treat. Skp2 functions as an oncogene that participates in processes of many cancers. Here, we report a novel Skp2 inhibitor AAA-237 that binds to Skp2 protein and inhibits the proliferation of the NSCLC cells. We further investigated the anti-NSCLC mechanism of AAA-237 and found that it arrested the cell cycle at the G0/G1 phase by targeting Skp2 to reduce the degradation of p21Cip1 and p27Kip1 or by transcriptionally activating FOXO1 to increase the mRNA expression of p21Cip1 and p27Kip1. More importantly, we found that treatment of a high concentration AAA-237 could induce apoptosis of NSCLC cells and treatment of a low AAA-237 concentration for a longer time could induce senescence of NSCLC cells. Similar results were found in nude mice xenografted with A549 cells. AAA-237 inhibited tumor growth by inducing apoptosis and senescence in a dose-dependent manner. Considering these results, we propose that AAA-237 could be a promising therapeutic drug for treating patients with NSCLC. Graphical Abstract: ga1